Biblical and classical myths the mythological framework of Western culture - Frye, Northrop; Macpherson, Jay. (Toronto ; Buffalo : University of Toronto Press, 2004)
"By complementing the Biblical tradition with the Classical, this volume provides a comprehensive introduction to Western mythology. Engaging and accessible, Biblical and Classical Myths represents a unique achievement in scholarship and is an essential volume for students and others interested in literature and cultural studies."--BOOK JACKET.
Symbolism in the Bible -- An Approach to the Bible and Translations of the Bible -- The Shape of the Bible -- Images of Paradise: Trees and Water -- Parody and Manifest Demonic: Trees and Water -- Sexual Imagery: The Bride and the Bridegroom; The Great Whore and the Forgiven Harlot -- Pastoral and Agricultural Imagery -- The World of Angels; Leviathan, Dragons, and the Antichrist -- Demonic Parodies and the Hero from across the Sea -- The Double Mirror: Exodus and Gospel -- The Metaphor of Kingship -- King, Priest, and Prophet -- The Question of Primogeniture -- Genesis: In the Beginning -- Genesis: Creating the Sexes; Exodus: A Revolutionary Heritage -- Law: Ordering a Society -- Law and Revolution; Wisdom: The Proverb -- Wisdom: Playing before God; Ecclesiastes: Vanity of Vanities -- Job: A Test -- Job and the Question of Tragedy -- Job and Restored Humanity -- The Language of Proclamation: Style and Rhythm in the Bible; The Gospel: Rewriting the Commandments -- Revelation: Removing the Veil -- Revelation: After the Ego Disappears -- The Language of Love -- Four Ages: The Classical Myths -- In The Beginning -- The Creation -- The Golden Age -- War in Heaven -- The Reign of Zeus -- Prometheus -- Pandora's Box -- Deucalion's Flood -- Phaethon -- Spring and Winter -- Demeter and Persephone -- Adonis -- Hyacinthus -- Narcissus -- Orpheus -- Loves of the Gods and Metamorphoses -- Loves of Zeus: Callisto, Io -- Pan and Syrinx -- Apollo and Daphne -- Clytie -- Endymion -- Arachne -- Procne and Philomela -- Midas' Touch -- Ceyx and Alcyone -- Nisus and Scylla -- Philemon and Baucis -- The Heroes -- Perseus -- The Labours of Heracles -- Jason and the Golden Fleece -- Bellerophon and Pegasus -- Theseus -- The Royal House of Thebes -- The Children of Agenor -- Zeus and Semele -- Ino and Athamas -- Pentheus -- Actaeon -- Oedipus -- The Tale of Troy -- The Apple of Discord -- The War -- The Fall of the City -- The Returns -- The Return of Menelaus -- The Return of Agamemnon -- The Return of Aeneas -- The Return of Odysseus -- Cupid and Psyche -- Conclusion: The Passing and Afterlife of the Gods -- Family Trees -- Mythology-History Chart.
Includes bibliographical references (p. [433]-435) and indexes.
Description based on print version record.
Keywords: Mythology, Classical; Myth in the Bible; Mythe dans la Bible; Mythologie ancienne; Mythologie; Oudheid; Bijbel; Mythologie classique; Mythe dans la Bible; Symbolisme dans la Bible; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books